Hierarchical nanorod-based TiO2 microspheres for superior electrochemical energy storage - Le, Thi Hang; Le, Thanh Son; Dien, Luong Xuan; Vo, Dai-Viet N.; Truong, Quang Duc (Elsevier B.V., 2018)
Nanorod-based rutile TiO2 microspheres composed of numerous single-crystalline nanorodsare successfully fabricated by hydrothermal treatment of peroxo titanic acid in acidic solution. The formation of highly oriented nanorod-based microspheres can be explained in view of crystal growth under the coordination chemistry rule, followed by particle attachment and coalescence. As anodes for Li-ion batteries, the TiO2 microsphere electrodes show enhanced rate performance, deliver a high reversible specific capacity of 180 mAh g−1 at 0.2 C (33.6 mA g−1) and 85.6 mAh g−1 at an extremely high rate of 50 C with an outstanding retention of 47.5%. These remarkable electrode properties are attributed to the efficient electron-transport by the hierarchical conductive pathway which promoted electronic conductivity and the shortened Li+ diffusion length resulting from the ultrafine nanorod structure.